Determining stability in connected speech in primary progressive aphasia and Alzheimer's disease. (4th May 2018) - Beales, Ashleigh; Whitworth, Anne; Cartwright, Jade; Panegyres, Peter K.; Kane, Robert T.
Abstract: Purpose : Using connected speech to assess progressive language disorders is confounded by uncertainty around whether connected speech is stable over successive sampling, and therefore representative of an individual's performance, and whether some contexts and/or language behaviours show greater stability than others. Method : A repeated measure, within groups, research design was used to investigate stability of a range of behaviours in the connected speech of six individuals with primary progressive aphasia and three individuals with Alzheimer's disease. Stability was evaluated, at a group and individual level, across three samples, collected over 3 weeks, involving everyday monologue, narrative and picture description, and analysed for lexical content, fluency and communicative informativeness and efficiency. Result : Excellent and significant stability was found on the majority of measures, at a group and individual level, across all genres, with isolated measures (e.g. nouns use, communicative efficiency) showing good, but greater variability, within one of the three genres. Conclusion : Findings provide evidence of stability on measures of lexical content, fluency and communicative informativeness and efficiency. While preliminary evidence suggests that task selection is influential when considering stability of particular connected speech measures, replication over a larger sample is necessary to reproduce findings.